A qualitative descriptive study of a novel nurse-led skin cancer screening model in rural Australia - Kristen Glenister; Sophie Witherspoon; Alan Crouch (BMC, 2022)
Abstract Background People residing in rural areas have higher rates of skin cancer and face barriers to accessing care. Models of skin cancer care addressing the specific needs of rural communities and overcoming specific challenges are required, but literature is scarce. This study aimed to describe the elements of a nurse-led skin cancer model in rural Victoria using qualitative methodology and programme logic to inform implementation and ongoing sustainability. Methods Qualitative descriptive design. Semi-structured interviews were conducted with key stakeholders involved in the skin cancer model, namely health service executive management, clinical staff, and administration staff. Interviews were audio-recorded and transcribed verbatim. Transcripts were thematically analysed independently by two researchers before themes were compared and refined. A programme logic model was developed to organise themes into contextual elements, inputs, activities and anticipated outcomes; it was also used as a visual tool to aid discussions with key stakeholders. Member checking of the logic model occurred to verify interpretation. This programme logic model will be refined throughout the implementation phase, and again after three years of service delivery. Results Eight stakeholders participated in interviews. Thematic analysis identified three major themes: the influence of the local rural context, the elements of the model, and "making it happen'. These major themes and accompanying sub-themes were mapped to the programme logic model by contextual elements (rural locale, health service access barriers, burden of disease), key inputs (promotion, human resources including appropriate nurse training and leadership) and 'making it happen' (governance including referral pathways, flexible and sustained funding, and partnerships). The anticipated outcomes identified include skin cancer care delivered locally, timely access, career development for nurses, and decreased skin cancer burden. Conclusion An initiative that is place-based and community driven in response to consumer demand addresses key system barriers to earlier detection of skin cancers. It is anticipated to result in flow-on reductions in skin cancer disease burden. Programme logic was useful to both describe the initiative and as a visual tool for discussions, with the potential to inform wider health service efforts to address system barriers and bottlenecks.